Pro- and anti-inflammatory cytokines and growth factors in patients undergoing in vitro fertilization procedure treated with prednisone - Piekarska, Karolina; Dratwa, Marta; Radwan, Paweł; Radwan, Michał; Bogunia-Kubik, Katarzyna; Nowak, Izabela (Frontiers in Immunology, 2023)
Embryo implantation is a key moment in pregnancy. Abnormal production of pro- and anti-inflammatory cytokines, their receptors and other immune factors may result in embryo implantation failure and pregnancy loss. The aim of this study was to determine the profile of selected pro- and anti-inflammatory factors in the blood plasma of patients undergoing in vitro fertilization (IVF) and control women who achieved pregnancy after natural conception. The examined patients were administered steroid prednisone. We present results concern the plasma levels of IFN-ɣ, BDNF, LIF, VEGF-A, sTNFR1 and IL-10. We found that IVF patients receiving steroids differed significantly from patients who were not administered such treatment in terms of IFN-γ and IL-10 levels. Moreover, IVF patients differed in secretion of all tested factors with the fertile controls. Our results indicated that women who secrete at least 1409 pg/ml of sTNFR1 have a chance to become pregnant naturally and give birth to a child, while patients after IVF must achieve a concentration of 962.3 pg/ml sTNFR1 in blood plasma for successful pregnancy. In addition, IVF patients secreting VEGF-A above 43.28 pg/ml have a greater risk of miscarriage or a failed transfer in comparison to women secreting below this value. In conclusion, fertile women present a different profile of pro- and anti-inflammatory cytokines, and growth factors compared to patients with recurrent implantation failure (RIF).